A behavioral equation framework for time-domain transmissibilities. (April 2017) - Aljanaideh, Khaled F.; Bernstein, Dennis S.
Abstract: Transmissibilities are widely used in engineering to express the relationship between sets of signals that are not necessarily inputs and outputs in the usual causal sense. Despite their usefulness, a rigorous intellectual framework for transmissibilities has been lacking. In this paper we demonstrate that behavioral equations provide a suitable framework for time-domain transmissibilities by choosing the latent variables in the behavioral equations to be the external signals that drive the system. This connection provides a theoretical foundation for time-domain transmissibilities and demonstrates the relevance of behavioral modeling to an important class of applications.